X-ray photoemission and absorption study of the pyrochlore iridates (Eu1−xBix)2Ir2O7, 0 ⩽x ⩽ 1. (28th September 2022) - Telang, Prachi; Bandyopadhyay, Abhisek; Mishra, Kshiti; Rout, Dibyata; Bag, Rabindranath; Gloskovskii, A; Matveyev, Yu; Singh, Surjeet
Abstract: The pyrochlore iridates (Eu 1 − x Bi x )2 Ir2 O7 (0 ⩽ x ⩽ 1) undergo an anomalous negative lattice expansion for small Bi-doping ( x ⩽ 0.035 ) (region I) and a normal lattice expansion for x ⩾ 0.1 (region II); this is accompanied by a transition from an insulating (and magnetically ordered) to a metallic (and with no magnetic ordering) ground state. Here, we investigate (Eu 1 − x Bi x )2 Ir2 O7 (0 ⩽ x ⩽ 1) using hard x-ray photoemission spectroscopy and x-ray absorption fine structure (XAFS) spectroscopy. By analyzing the Eu- L 3, Ir- L 3 and Bi- L 2 & L 3 edges x-ray absorption near edge structure spectra and Eu-3 d core-level XPS spectra, we show that the metal cations retain their nominal valence, namely, Ir 4+, Bi 3+ and Eu 3+, respectively, throughout the series. The Ir-4 f and Bi-4 f core-level XPS spectra consist of screened and unscreened doublets. The unscreened component is dominant In the insulating range ( x ⩽ 0.035 ), and in the metallic region ( x ⩾ 0.1 ), the screened component dominates the spectra. The Eu-3 d core-level spectra remain invariant under Bi doping. The extended XAFS data show that the coordination around the Ir remains well preserved throughout the series. The evolution of the valence band spectra near the Fermi energy with increasing Bi doping indicates the presence of strong Ir(5d)–Bi(6p) hybridization which drives the metal-to-insulator transition.